Suicide in rural agrarian culture: revealing the micro dimensions of suicidal behavior in Gunungkidul Regency, Indonesia - Cahyono, Sunit Agus Tri; Wahyono, Eko; Ikawati, Ikawati; Purnama, Akhmad; Tursilarini, Tateki Yoga; Murtiwidayanti, Sri Yuni; Listyawati, Andayani; Udiati, Trilaksmi; Suryani, Suryani; Gutomo, Tri; Hidayatulloh, A. Nururrochman; Irmawan, Irmawan; et al. (Frontiers in Sociology, 2025)
BackgroundSuicide is a serious and complex global public health problem, affecting individuals from diverse social backgrounds, genders, and ages. Gunungkidul Regency in the Special Region of Yogyakarta, Indonesia, has the highest suicide rate in the region, making it a crucial location for understanding the contributing factors to suicide in a rural, agrarian cultural context.MethodsThis study employed a qualitative descriptive design with a naturalistic approach to understand the meaning of individuals’ lived experiences in their natural context without researcher intervention. Data were collected through semi-structured interviews with 21 participants, consisting of 15 family members of individuals who died by suicide and six community stakeholders (community leaders, religious leaders, health workers, NGO representatives, local police officers, and village administrators). All interviews were audio-recorded, transcribed verbatim, and analyzed using an inductive thematic approach. Two researchers conducted coding independently, with validation through peer discussions, triangulation of interview data, field notes, and document review to ensure the credibility of the findings.ResultsThe analysis revealed two main patterns of suicide: altruistic suicide, associated with strong social cohesion, found in Playen, Wonosari, and Karangmojo sub-districts; and egoistic suicide, reflecting weak social ties, found in Semin and Ngawen. Contributing micro-factors include depression, economic stress, and chronic illness, which mutually exacerbate an individual’s psychological state. Seasonal stress, such as crop failure during a prolonged dry season, increases the risk. In local culture, suicide is sometimes interpreted as a form of “rebellion” against religious and social norms.ConclusionThese findings demonstrate the importance of early detection of mental health disorders, community economic empowerment through cooperatives, and culturally based education to address myths and stigma surrounding suicide. Prevention efforts must consider agrarian communities’ social and cultural context more deeply.